Draft Five Year Plan 1978-83 Youth Welfare Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The main objectives of the department are to plan and promote sports activities in the State in consultation with the Council of Sports and develop youth welfare services for all round development of youths on the advice of the Youth Board constituted under the Chairmanship of Chief Minister. The sports and youth welfare activites are conducted outside schools and colleges touching the non-student youths.
Government of Madhya Pradesh, Planning, Economics and Statistics Department